THE PALACES OF THE M'ZAB VALLEY BETWEEN THE PAST AND THE PRESENT. A CASE STUDY OF THE PALACE OF ELATTEF - GHARDAIA PROVINCE, ALGERIA - Bahi Saida,; Lakhdar Ammar,; Mohamed Baadeche,; Haouari Souad, (International Journal of Innovative Technologies in Social Science, 2024)
This research paper aims to study the past and present of the palaces of the M'zab Valley, which were classified as a World Urban Heritage site in 1982 due to their unique and distinguished architectural and urban characteristics. The palaces of the M'zab Valley have maintained their style throughout the historical periods they have passed through. However, in recent times, they have struggled to withstand environmental, demographic, and socio-economic factors, leading to noticeable changes and distortions in the old buildings and the urban fabric. To study this situation, we have chosen the Palace of El Atteuf, one of the oldest palaces and the cornerstone of the settlement of the M'zab Valley, as a case study. In this research, we adopted two methodologies: the historical approach, through which we will study the past of the palace, and the descriptive-analytical approach, along with fieldwork conducted in 2002. We selected a random sample of 100 residents, which will assist us in the analytical study of the palace's current situation.